Enhancing EFL Students’ Recount Writing: A Comparative Analysis of Grammarly, QuillBot, and GrammarCheck Applications - Ismailia, Titik; Novawan, Adriadi (Politeknik Negeri Jember, 2025)
This study examines the effectiveness of three AI-powered grammar checker applications—Grammarly, QuillBot, and GrammarCheck—in improving the recount writing skills of EFL students. Fifty-two undergraduate students revised their recount texts using these tools, and data were collected through text analysis and student questionnaires. Results show that all three applications helped reduce grammatical errors and increased students’ awareness of language accuracy, with Grammarly offering the most comprehensive feedback and QuillBot providing valuable paraphrasing support. Despite their benefits, limitations such as surface-level corrections and restricted free features highlight the need for integrating these tools alongside teacher guidance. The findings suggest that grammar checkers can serve as effective supplementary aids in EFL writing instruction when used thoughtfully.